HADITH-HADITH DALAM BUKU MOTIVASI DI MALAYSIA (KAJIAN SANAD DAN MATAN) - Muhammad Faiz Fathi Asmori (Pascasarjana UIN ANTASARI Banjarmasin, 2017)
This article presents the research methodology of hadith in the motivation books in Malaysia. There are ten books have been collected and 149 of hadith that have been research in this study. However, the researchers only studied 123 hadith, while 26 hadith are repeated. Based on the analysis of the status of 123 hadith, the researchers found 75 hadith were rated as maqbul hadith (Sahih and hasan), 42 hadith have had on the chain (sanad), and the remaining 6 hadith undetermined status. This study is a contribution to the writing of Islamic studies to enable the reader to know the status of the hadith set forth in motivational books whether it is accepted or rejected. In addition, this study also provides a set of guidelines for writers of motivational books genre to present hadith into their works. It would be beneficial to authors who have no background in Islamic studies and studies of hadith in producing better quality.